Internal Information Quality and State Tax Planning* - Laplante, Stacie Kelley; Lynch, Daniel P.; Vernon, Mary E. (Contemporary Accounting Research, 2021)
ABSTRACT This study examines the association between internal information quality and state tax planning. Prior literature documents a positive association between internal information quality and summary measures of tax avoidance. However, we know little about specific forms of tax planning and internal information quality. State tax planning is difficult because of the number of jurisdictions, variety of tax rules, variation of enforcement, and apportionment requirements. We find that internal information quality facilitates state tax planning and is most important when firms face more restrictive state tax laws and when domestic firms relative to multinational firms have international income shifting opportunities. Our results provide a baseline of the economic effects of internal information quality on different forms of tax planning. Understanding internal information quality's role in state tax planning is especially relevant as countries propose to modify international tax rules to mirror the state taxation format of a single‐entity system with apportionment.